Proposal of a prevention´s program of injuries in female volleyball infantil and cadete - Del Castillo-Andrés, O.; Toronjo-Hornillo, L.; Moya-Martínez, I.; Campos-Mesa, M. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2019)
The aim of this study is to analyze the motor response of two groups of volleyball players of compulsory secondary education, before an unintentional fall of the back, and to determine what effects are observed in the fall after participating in the program Safe Fall-Safe Schools©. A quasi-experimental research has been applied to 27 players, between the ages of 13 and 16, who practice as an extra-curricular volleyball activity in the I.E.S. Ramón y Cajal de Tocina, Seville, Spain. The data was collected before and after the intervention, using the INFOSECA ad hoc observation scale. Descriptive and correlational statistics were applied. The criterion to consider the statistical significance was p <0.05 (McNemar test). The results obtained indicate that through the implementation of the program it is possible to assimilate successfully the technical movements associated with a fall backwards that contribute to increase the protection and safety of the minors athletes.